Simulation on contraction flow of concentrated cellulose/1-butyl-3-methylimidazolium chloride solution through spinneret orifice. (May 2014) - Xia, X. L.; Yao, Y. B.; Zhu, X. J.; Mukuze, K. S.; Wang, C. S.; Zhang, Y. M.; Wang, H. P.
<x content-type="archive" xml:space="preserve">Abstract</x> Concentrated cellulose/1-butyl-3-methylimidazolium chloride ([bmim]Cl) solution which exhibits typical elasticity has been employed to prepare fibres by dry jet wet spinning technique. In order to design the spinneret, simulation on contraction flow of cellulose/[bmim]Cl solution through spinneret orifice was carried out. Geometry and mathematical models were established according to rheological behaviour and material parameters. The effects of geometry on variation of viscosity and flow pattern were simulated and discussed. The results show that an increase in aspect ratio decreased the apparent viscosity and a decrease in entrance angle reduced the size of 'dead' region. The aspect ratio and entrance angle of spinneret during dry jet wet spinning were optimised.